A case report of duodenal carcinoid tumor causing gastric outlet obstruction - Shaikh, Aftab; Sholapur, Sachin; Tandur, Amarjeet (International Surgery Journal, 2021)
Carcinoids are tumours of neuroendocrine origin. Commonly found in gastrointestinal and respiratory tracts, however, duodenal carcinoids among them are comparatively rare. Duodenal carcinoids presenting as acute gastric outlet obstruction are even rarer. Clinically difficult to diagnose due to their non-specific presentation. Endoscopic ultrasound (EUS), computed tomography (CT) and immunohistochemistry (IHC) for markers like chromogranin A, neuron specific enolase (NSE), synaptophysin helps in making a definitive diagnosis. Management is influenced by multiple factors like size, site, metastases and regional lymph node involvement. Here is a case report of solitary duodenal carcinoid complicated with acute gastric outlet obstruction. A middle-aged female with chronic history of intractable dyspepsia, bloating and occasional vomiting, on thorough evaluation with upper GI endoscopy, EUS guided biopsy, CT scan and histopathological examination was diagnosed of a solitary 2.2×1.2×1.6 cm sized duodenal carcinoid tumour. Patient had no past, family or genetic history supporting the diagnosis. Patient presented with features of acute gastric outlet obstruction 1 week after the diagnosis which required a distal gastrectomy with resection of first part of duodenum followed by a Roux-en-Y gastrojejunostomy with an uneventful 6 month follow up. As the size in this case was more than 2 cm with AJCC staging of T2N0M0, distal gastrectomy with Roux-en-Y gastrojejunostomy was done to ensure an R0 resection and to relieve the gastric outlet obstruction. Duodenal carcinoids presenting as gastric outlet obstruction are not common. Early management is essential to prevent complications like gastric outlet obstruction despite of indolent course of the disease.